2022
DOI: 10.3389/fphar.2022.1037893
|View full text |Cite
|
Sign up to set email alerts
|

Association between different concentrations of human serum albumin and 28-day mortality in intensive care patients with sepsis: A propensity score matching analysis

Abstract: Background: Human serum albumin (HSA) is a commonly used medication for the treatment of sepsis. However, there is no conclusive evidence as to whether different concentrations of HSA are associated with patient prognosis. This study aimed to evaluate the association between different concentrations of HSA and 28-day mortality in patients with sepsis.Methods: The data for this retrospective study were collected from the Medical Information Mart for Intensive Care IV database. Patients with sepsis were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Sepsis is still the leading cause of death in patients elected to the ICU (15,18). In the present study, the 28-day mortality rate of septic patients with DM was 23.9% (n=533), which was higher than in general septic patients (10%-15%) (34)(35)(36). Regarding the hospitalization characteristics of the study population, we observed that survivors showed longer hospital and ICU stays than non-survivors, which was consistent with previous studies (24, 37).…”
Section: Discussionmentioning
confidence: 45%
“…Sepsis is still the leading cause of death in patients elected to the ICU (15,18). In the present study, the 28-day mortality rate of septic patients with DM was 23.9% (n=533), which was higher than in general septic patients (10%-15%) (34)(35)(36). Regarding the hospitalization characteristics of the study population, we observed that survivors showed longer hospital and ICU stays than non-survivors, which was consistent with previous studies (24, 37).…”
Section: Discussionmentioning
confidence: 45%
“…HSA regulates the blood osmotic pressure [ 87 ] and improves edema, hypoalbuminemia, glycocalyx degradation and hypovolemia caused by sepsis. A retrospective study involving 5009 patients with sepsis demonstrated that treatment with 5% HSA significantly reduced sepsis-related 28-day mortality (8.7%) [ 45 ]. In addition, albumin can also reduce heme-induced hepatic sinusoidal contraction and cytotoxicity, and improve liver microcirculation and organ function by binding heme.…”
Section: Proteins and Peptidesmentioning
confidence: 99%